(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2025)
Local cattle in Indonesia generally have lower productivity and meat quality, so fulfilling high-quality meat needs still relies on imported supplies. The study aims to explore the potential of lower-quality local beef to be aged so that the quality of local meat can be improved with parameter observed WBSF value, pH value, water binding capacity and percentage of cooking loss. This study used the wet aging method and the chosen samples of Bali cattle, Ongole crossbred cattle and Simmental crossbred cattle with aging periods of 1 day, 7 days, 14 days, 21 days and 28 days. Data were analyzed using a split plot split in time design. The results showed that aging improves the physical qualities of the beef, namely a significant decrease in WBSF value, while pH value, water binding capacity and percentage of cooking shrinkage were still within the standard value range despite changes observed within the aging period. Bali cattle achieved tender category (3.9-4.4 kg cm-2) at 14 days aging period (4.08 kg cm-2), while Ongole and Simmental crossbreds achieved tender category at 21 days aging period (4.27 and 3.76 kg cm-2, respectively)